"Mi amerikaiak vagyunk..." John Reed haditudósítása a szerbiai hadszíntérről 1915-ben - Szabó Pál (2017)
John Reed, the well known American war correspondent and journalist, in 1915 arrived at the Serbian theatre of war, from where he reported the American Metropolitan Magazine. In his vivid reportage he painted from dramatic perspective the everyday life of the people along the battle-line, but the atrocities committed by the Hungarians, therefore it adds important contribution – from an Americo–Serbian aspect – to more objective judgement of the events of the first World War in the Balkans.